THE ROLE OF PSYCHOLOGICAL CAPITAL AS A PREDICTOR OF NURSES' ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN REGIONAL HOSPITALS - Yuliani, Eka (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Nurses, as the frontline of healthcare services, are expected to deliver optimal performance that frequently goes beyond their formal duties, thus requiring robust psychological capital to support voluntary work behaviors known as Organizational Citizenship Behavior (OCB). This study aims to analyze the effect of Psychological Capital (PsyCap), which comprises hope, efficacy, resilience, and optimism, on nurses' OCB in regional hospitals and to identify the most dominant dimension influencing OCB. Employing a quantitative correlational approach, this research collected primary data through structured questionnaires distributed to nurses as respondents. The data were analyzed using descriptive statistics, multiple regression analysis, and moderated regression analysis to test variable relationships and the moderating effects of demographic factors. The results indicate that the levels of PsyCap and OCB among nurses are relatively high, with resilience emerging as the most significant predictor of OCB. These findings strengthen the position of PsyCap as an essential psychological resource that fosters prosocial behaviors among nurses, especially in regional hospitals often challenged by limited human resources. The implications suggest that hospital management should design PsyCap enhancement programs, focusing particularly on strengthening nurses' mental resilience to sustainably improve healthcare service quality. This study also contributes theoretically by enriching the literature on organizational behavior within the Indonesian healthcare sector.